Perspectives of renewable energy usage in Turkey: how far - how close to EU standards - Gonel, Feride Doganer (INDERSCIENCE ENTERPRISES LTD, 2006)
Turkey has initiated some activities in using renewable energy sources (RES) by taking measures to address environmental problems and energy security. However, the integration of energy-environment strategy in Turkey has faced serious challenges. The aim of this article is to study the obstacles and success conditions for RES in Turkey and to compare with other newly accession and candidate countries in the context of European Union (EU)'s renewable energy policy. The first part of the paper provides an overview of EU policies for renewable energy. In the second part, after explaining Turkey's energy policy, we concentrate on the determinants of the demand and supply for RES and aim to provide an understanding of the energy linkages between Turkey and EU. Beside the other candidates' renewable energy situations, the differences between Turkey - EU-25 and other candidates - EU-25 are examined as the subject of the third and conclusion part of the study.
Keywords: renewable energy; European Union (EU); Turkey; energy policy; environmental protection; Business & Economics; Environmental Sciences & Ecology